Efeitos da suplementação de bicarbonato de sódio no desempenho físico e em variáveis cardiovasculares em adultos de meia idade e idosos com DIabetes Mellitus tipo 2 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The epidemic of diabetes mellitus (DM) represents a threat to health on a global scale. Physical exercise is recognized as an important non-pharmacological pillar in the prevention and treatment of type 2 DM (T2DM), providing a series of acute and chronic benefits. However, considering the limitations imposed by the disease condition, the use of additional resources, such as supplementation with sodium bicarbonate (SB), may be a strategy to improve physical performance in high-intensity protocols, which, in turn, have shown numerous benefits in individuals with T2DM. Therefore, the aim of this study was to analyze physical performance, blood glucose, and cardiovascular parameters after acute SB supplementation in middle-aged and elderly adults with T2DM. The sample consisted of 13 individuals (age: 62.15 ± 6.90 years; BMI: 29.14 ± 4.49 kg/m2 ) with a mean disease duration of 5.03 ± 6.64 years. The maximal incremental test (MIT) was performed in the presence of SB or placebo, which was administered 60 minutes before the experimental sessions. Additionally, there was pre- and post-test monitoring of blood pressure (BP), heart rate (HR), and capillary blood glucose. The study revealed statistically significant differences in MIT in the SB condition compared to placebo (SB: 481 ± 116 seconds and placebo: 439 ± 99 seconds, p = 0.005) and in blood glucose levels in both pre- and post-test conditions (p = 0.0001). No statistically significant differences were found between conditions or over time in the BP, chronotropic reserve, and peak and recovery HR variables (p > 0.05). Although no significant differences were identified in the cardiovascular variables between the evaluated conditions, there was a significant increase in test time in the SB supplementation condition, along with a reduction in capillary blood glucose in both conditions. These results suggest that SB supplementation may be safe and effective for people with T2DM, providing additional benefits to physical performance considering the test time increase and the fatigue reduction.
Keywords: exercício físico; tampões; ergogênico; fadiga; physical exercise; buffers; ergogenic; fatigue; CNPQ::CIENCIAS DA SAUDE